DUA SISTEM TUBUH: REPRODUKSI DAN ENDOKRIN - HAVIZ, M. (Sainstek : Jurnal Sains dan Teknologi, 2013)
Why is it important reproductive and endocrine system is important for someone to be learned by studying embryology? Both of these systems, reproductive and endocrine systems are the most interconnected in the study of embryology. For example, when spermatogenesis (sperm for-mation process), will be studied how the male sex glands as the production of sperm, and then at the end of the study as well as the hormonal regulation of spermatogenesis. In the second chapter of this book discussed on the reproductive system, including ultra structure and fsiologis of male and female reproductive systems. In the next section, is also discussed about the endocrine system. Discussion of the endocrine system include terminology, structure, function and mechanism of action of several hormones related to reproductive system and embryology.Key words: reproduction, endocrine, hormone